Systematic bibliographic review applied to the brazilian footwear sector - Lima, Paulo Fernando; Costa, Vera Mariza Henriques de Miranda [UNESP] (Sindicato Secretarias Estado Sao Paulo, 2023)
The retraction in the footwear industry raises concern among researchers, who seek to investigate the operating conditions and the dynamics of this sector, aiming to propose improvement actions. In this context, this article was elaborated from a systematic bibliographic review carried out in the annals of SIMPEP, period 2007-2018, with the following objective: to locate articles about the footwear sector present in these annals, to classify them in relation to their distribution by Production Engineering areas and identify its contribution to the knowledge of management and the recent dynamics of this sector. We found 66 articles, 63.64% of which were present in areas 1 -production management and 7 -strategic and organizational management. Twenty-eigth articles were selected, which made it possible to confirm important contributions, both theoretical and practical, to the management knowledge and the recent dynamics of the Brazilian footwear sector.
Keywords: Footwear Sector; Systematic Bibliographic Review; Annals of SIMPEP